No good deed goes unpunished: the social costs of prosocial behaviour. (21st July 2021) - Raihani, Nichola J.; Power, Eleanor A.
Abstract: Abstract: Performing costly helpful behaviours can allow individuals to improve their reputation. Those who gain a good reputation are often preferred as interaction partners and are consequently better able to access support through cooperative relationships with others. However, investing in prosocial displays can sometimes yield social costs: excessively generous individuals risk losing their good reputation, and even being vilified, ostracised or antisocially punished. As a consequence, people frequently try to downplay their prosocial actions or hide them from others. In this review, we explore when and why investments in prosocial behaviour are likely to yield social costs. We propose two key features of interactions that make it more likely that generous individuals will incur social costs when: (a) observers infer that helpful behaviour is motivated by strategic or selfish motives; and (b) observers infer that helpful behaviour is detrimental to them. We describe how the cognition required to consider ulterior motives emerges over development and how these tendencies vary across cultures – and discuss how the potential for helpful actions to result in social costs might place boundaries on prosocial behaviour as well as limiting the contexts in which it might occur. We end by outlining the key avenues and priorities for future research.